Teologi Filantropi Sebagai Basis Persahabatan Antarpenganut Agama: Sebuah Analisis Biblika Terhadap Kisah Para Rasul 28:1-2, 7-10, Dan Titus 3:1-10: Theology Of Philanthropy As A Basis Of Interreligious Friendship: A Biblical Analysis Of Acts 28:1-2; 7-10, And Titus 3:1-10 - Christanto Sema Rappan Paledung (Societas Dei: Jurnal Agama dan Masyarakat, 2021)
Today philanthropy is always understood as the charity acts towards the poor. Many social organizations are active in the philanthropy field. However, these philanthropic acts only represent charitable or charity acts. Therefore, this paper intends to explore the biblical meaning of philanthropyitself. It will construct a theology of philanthropy according to the interpretation of Acts 28:1-2, 7-10 and Titus 3:1-10. The main author’s argument in this paper is that philanthropic theology is an act of friendship between God and humans also human to human which is the church basis and character, in relationships with other religions. This research process will use library research and hermeneutical processes to explore the meaning of the philanthropy concept. In the end, I will propose the implication of philanthropy theology in daily life with other religions. Keywords: Philanthropy; Friendship; God; Human; Life With Other Religions.